Presidential Address: The Invisible Historian - Miller, J. (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 1997)
AbstractAlthough contemporary events have made it appear that there is widespread support in Canada for history as a discipline, the reality is otherwise. Many individuals, interest groups, and even institutions make considerable use of historical arguments in public debate to advance their causes, it is true. However, it is almost invariably the case that these advocates making historical arguments are not historians. This painful reality was brought home to the historical profession in 1996-97 by such events as the release of the Final Report of the Royal Commission on Aboriginal Peoples and the debates over public policy issues such as copyright reform and a protocol for research involving humans. It is essential to the future of the discipline and of organisations such as CHAJSHC that historians reassert their role in the processes of researching, interpeting, and utilizing history in public discourse and academic arenas.